A New Study on Generalized Absolute Matrix Summability - í–zarslan, Hikmet Seyhan (Communications in Mathematics and Applications, 2016)
In this paper, a general theorem on \(| A,p_n;δ|_k\) summability factors, which generalizes a theorem of Bor [4] on \(|N,p_n|_k\) summability factors, has been proved by using almost increasing sequences.